Therapeutic ultrasound and essential oil of melaleuca alternifolia interfere with muscle regeneration? (Research, Society and Development, 2022)
Currently the Essentials oil of Tea Tree is used in healing, for possessing various medicinal properties. Phonophoresis is a method used in physiotherapy, where pharmacological substances associated with a coupling agent, are induced by ultrasonic waves in the underlying tissues. Our objectives are aimed at monitoring and qualitative analysis of the lesion treated with the compound and the method accuracy phonophoresis. We used twenty (20) rats, which are divided into two (2) different groups: Group I: Rats harmed without intervention and Group II: Rats victims treated with the compound by Phonophoresis. Histological analysis showed the material collected in samples from animals in group I, an extensive and diffuse inflammation, unconnected with large amounts of inflammatory cells, as in group 2 inflammation comes in mild areas with limited, there is also muscle fiber regeneration. The results seem to demonstrate the efficacy of Melaleuca alternifolia essential oil by phonophoresis in the muscle fiber in the lesion region.